2017
DOI: 10.15376/biores.12.4.8106-8118
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical properties of OSB boards versus equilibrium moisture content

Abstract: The basic thermophysical properties of oriented strand boards were determined experimentally for use in humid conditions (OSB3) depending on the moisture content. The dependency between the thermal conductivity, thermal diffusivity, specific heat capacity, and the moisture content in the range of 0% to 10%, was examined. The non-stationary extended dynamic plane source (EDPS) experimental method was used. EDPS method was modified for anisotropic materials, i.e. with special considerations of heat-loss effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…The volume specific heat of the wood samples in the radial direction were: softwood -spruce (0.503-0.575 10 6 J m -3 K -1 ), black pine (0.582-0.664 10 6 J m -3 K -1 ), hardwood -beech (0.758-0.820 10 6 J m -3 K -1 ), oak (0.813-0.890) 10 6 J m -3 K -1 ) and medium hardwood -chestnut (0.649-0.728 10 6 J m -3 K -1 ). In the literature, the values of mass specific heat were presented by Glass and Zelinka, (2010), Peere and Keey (2014), Radmanović et al (2014) and Igaz et al (2017), so in order to make a data comparison the values of volume specific heat were divided by the density of the wood sample, the partial results are in good agreement with the values presented in the literature by Czajkowski et al (2016), Sonderegger et al (2011 and Kühlmann (1962). They reported that the cause of various values of thermal parameters in the tangential and radial directions of the hardwood samples (oak, beech) is high-density wood fibre, but on the other hand, in the samples of softwood (spruce, pine) it is the low density of wood fibre.…”
Section: Coefficients Of Regression Equation (1)supporting
confidence: 65%
“…The volume specific heat of the wood samples in the radial direction were: softwood -spruce (0.503-0.575 10 6 J m -3 K -1 ), black pine (0.582-0.664 10 6 J m -3 K -1 ), hardwood -beech (0.758-0.820 10 6 J m -3 K -1 ), oak (0.813-0.890) 10 6 J m -3 K -1 ) and medium hardwood -chestnut (0.649-0.728 10 6 J m -3 K -1 ). In the literature, the values of mass specific heat were presented by Glass and Zelinka, (2010), Peere and Keey (2014), Radmanović et al (2014) and Igaz et al (2017), so in order to make a data comparison the values of volume specific heat were divided by the density of the wood sample, the partial results are in good agreement with the values presented in the literature by Czajkowski et al (2016), Sonderegger et al (2011 and Kühlmann (1962). They reported that the cause of various values of thermal parameters in the tangential and radial directions of the hardwood samples (oak, beech) is high-density wood fibre, but on the other hand, in the samples of softwood (spruce, pine) it is the low density of wood fibre.…”
Section: Coefficients Of Regression Equation (1)supporting
confidence: 65%
“…The EDPS (Extended Dynamic Plane Source) method was used to measure physical properties. It is one of the non-stationary methods for this purpose [32, EDPS method is based on the Dynamic Plane Source (DPS) method, andit can be investigate the thermal conductivity, thermal diffusivity and specific heat capacity conductivity materials (λ ≤ 2 W•m −1 •K −1 ) [34,35]. Figure 5 shows the device scheme The EDPS (Extended Dynamic Plane Source) method was used to measure thermophysical properties.…”
Section: Thermophysical Propertiesmentioning
confidence: 99%
“…It is one of the non-stationary methods for this purpose [32,33]. The EDPS method is based on the Dynamic Plane Source (DPS) method, andit can be used to investigate the thermal conductivity, thermal diffusivity and specific heat capacity of low-conductivity materials (λ ≤ 2 W•m −1 •K −1 ) [34,35]. Figure 5 shows the device scheme.…”
Section: Thermophysical Propertiesmentioning
confidence: 99%
“…Assuming an average bark content of 10%, around 150-180 × 10 6 m 3 bark is produced annually by industrial wood logs [19]. Except for energy generation, tree bark can be used as thermal insulating [22][23][24] and sound absorbing material [25,26] as fire-retardant panels [27], as single-layer [28,29] or 3-layers particleboard [30], medium density fibreboards [31] and oriented strand boards [32,33].…”
Section: Introductionmentioning
confidence: 99%